Toward accurate inferences of response class membership. Issue 1 (11th July 2019) - Warner, Christine A.; Hanley, Gregory P.; Landa, Robin K.; Ruppel, Kelsey W.; Rajaraman, Adithyan; Ghaemmaghami, Mahshid; Slaton, Jessica D.; Gover, Holly C.
Abstract : In their review of synthesis within the functional analysis (FA) literature, Slaton and Hanley (2018) reported that most synthesized contingency analyses have included multiple topographies of problem behavior in the reinforcement contingency class. This leaves the question of whether one, some, or all forms of problem behavior are sensitive to the synthesized reinforcement contingencies in published analyses. To address this ambiguity, all topographies of problem behavior that were reported by caregivers to co‐occur with the most concerning problem behavior were analyzed for 10 participants. We implemented extinction across one or more forms of problem behavior to determine whether all forms reported to co‐occur were sensitive to the same synthesized reinforcement contingency. For nine of 10 participants, the most concerning topographies were sensitive to the same synthesized reinforcement contingencies as the less concerning topographies (results were inconclusive for one). Implications for inferring response class membership from single analyses are discussed.